2013
DOI: 10.1186/1756-0500-6-138
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the Arabic version of osteoporosis knowledge assessment tool (OKAT) and the osteoporosis health belief scale (OHBS)

Abstract: BackgroundKnowledge and awareness about osteoporosis and its related risk factors are important contributors to osteoporosis preventive behavior. There is a need to assess the reliability of international osteoporosis-related knowledge and belief measurement tools in Arabic community. This study aimed to assess the reliability of the Arabic version of Osteoporosis Knowledge Assessment Tool (OKAT) and the Osteoporosis Health Belief Scale (OHBS) among Syrian women.MethodsThe study included two phases. The first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 15 publications
1
28
1
3
Order By: Relevance
“…Another study, by Sayed-Hassan and Bashour in 2013, assessed the reliability of the Arabic version of the OBHS tool by recruiting one hundred Syrian women. The results revealed that the tool in its Arabic version is both reliable and linguistically acceptable 13 . In addition, another study, by Abdulameer et al.…”
Section: Introductionmentioning
confidence: 81%
“…Another study, by Sayed-Hassan and Bashour in 2013, assessed the reliability of the Arabic version of the OBHS tool by recruiting one hundred Syrian women. The results revealed that the tool in its Arabic version is both reliable and linguistically acceptable 13 . In addition, another study, by Abdulameer et al.…”
Section: Introductionmentioning
confidence: 81%
“…The OKT and OHBS had been translated into different languages and were found reliable and valid in different communities [ 32 , 39 42 ]. The Arabic version of OKT and OHBS had been previously published and found to be reliable and acceptable [ 43 ]. We used the Arabic version of published OKT and OHBS after introduction of certain minor language changes to suite the Arabic accent of Palestinian culture.…”
Section: Methodsmentioning
confidence: 99%
“…The fundamental requirement for managing any health disorder begins with the assessment of the existing awareness of the disorder within the target subjects residing in a region. Knowledge and awareness about the risk factors for osteoporosis are important for the prevention and management of the disease as there is evidence suggesting that knowledge and awareness is a contributor to osteoporosis prevention [4]. Also, healthy behaviors and lifestyle are associated with decreased risk of osteoporosis and its fracture risk as many studies suggested [4].…”
Section: Introductionmentioning
confidence: 99%